Passing efficacy of young basketball players: test or observation? - Sachanidi, M.; Apostolidis, N.; Chatzicharistos, D.; Bolatoglou, T. (International Journal of Performance Analysis in Sport, 2013)
Basketball is a combined game demanding elevated physical and technical skills, mental characteristics and tactical behaviour. These characteristics cannot be evaluated only by skill tests, which are considered inadequate to record the mental ability of the athletes. For the complete evaluation of the athletes' performance observation methods have been proposed, which record all of their efforts during the game. The aim of the present study was to evaluate the athletes' efficacy in passing skill, with two different methods: (a) the skill test and (b) game observation and correlate the results with the total game performance. For this purpose three basketball teams composed by 33 athletes, aged 14-15 years old, participated in the study. Initially, the athletes performed the passing test and afterwards in order to evaluate their passing efficacy and their overall performance, three games between the teams were recorded. Results indicated that performance in passing skill test was not correlated with passing efficacy or with total performance in the games. On the contrary, passing efficacy in the games was significantly correlated and could clearly predict the overall performance of the athlete. The athletes' performance in passing skill should not be evaluated only by application of test, but additionally by observation of the games.